2021
DOI: 10.1136/bmjopen-2020-042954
|View full text |Cite
|
Sign up to set email alerts
|

How can the uptake of preventive behaviour during the COVID-19 outbreak be improved? An online survey of 4827 Chinese residents

Abstract: ObjectivesThe aims of this study were to assess the uptake of preventive behaviour during the COVID-19 outbreak and to investigate the factors influencing the uptake of preventive behaviour based on the theory of planned behaviour (TPB).Design, setting and participantsA cross-sectional online survey was conducted among Chinese residents aged ≥18 years and 4827 participants from 31 provinces and autonomous regions were included in the current study. Uptake of preventive behaviour, attitude towards the spread of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…Although there is little research investigating locus of control with respect to COVID‐19, at least one study has suggested that internal locus of control is associated with intending to engage in various behaviours including handwashing, social distancing, wearing a face covering, and staying at home apart from essential reasons (Devereux, Miller, & Kirshenbaum, 2021). Perceived behavioural control was also the strongest predictor of high uptake of preventive behaviours in a separate study after adjusting for socio‐demographic characteristics, perceiving risk, attitudes towards the behaviour, and subjective norms (Mao et al., 2021). Potentially, focussing on someone’s agency in preventing the spread of infection may be a useful strategy for communications around test, trace, and isolate (Porat, Nyrup, Calvo, Paudyal, & Ford, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is little research investigating locus of control with respect to COVID‐19, at least one study has suggested that internal locus of control is associated with intending to engage in various behaviours including handwashing, social distancing, wearing a face covering, and staying at home apart from essential reasons (Devereux, Miller, & Kirshenbaum, 2021). Perceived behavioural control was also the strongest predictor of high uptake of preventive behaviours in a separate study after adjusting for socio‐demographic characteristics, perceiving risk, attitudes towards the behaviour, and subjective norms (Mao et al., 2021). Potentially, focussing on someone’s agency in preventing the spread of infection may be a useful strategy for communications around test, trace, and isolate (Porat, Nyrup, Calvo, Paudyal, & Ford, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Further, practitioners and researchers may want to consider the nuanced dynamics of fear, when fear may not be equally applied to others (particularly those who are immunocompromised or otherwise at risk) and oneself, limiting its influence on personal behaviors. Alternative methods, such as changing negative attitudes about prevention behaviors and improving subjective norms [ 34 ], should be explored for their feasibility and effectiveness in altering prevention behaviors in the context of COVID-19. Enlisting opinion leaders within communities disproportionately affected by COVID-19 is critical in this effort, as opinion leaders can act as gatekeepers for prevention efforts, help change social norms, and accelerate behavior change [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient knowledge provides an understanding of certain situations, including dealing with the COVID-19 pandemic. Understanding the situation provides selfconfidence so that it is not easily provoked or manipulated by invalid or overclaimed information (Mao et al, 2021) Behavioral changes require information about potential threats to the health of oneself or others. Valid information and increased knowledge affect handling the COVID-19 pandemic (Azlan et al, 2020;Chesser et al, 2020;Šuriņa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%